Development of low-fat fried fish using a two-prong strategy - Malak H. Azahrani; Daniel Ananey-Obiri; Lovie Matthews; Reza Tahergorabi (CyTA - Journal of Food, 2019)
In this study, a two-prong strategy was devised to reduce fat-uptake in deep-fat fried fish by developing a low cost, sustainable and product-friendly edible coating using fish processing by-products and replacement of corn starch in batter with sweet potato starch. Edible coatings (protein concentrations of 0, 5%, 10%, and 15%) were prepared from fish protein isolates using isoelectric solubilization and precipitation. Coating with 15% protein and sweet potato starch-based batter resulted in the highest reduction of fat-uptake and moisture loss of fried fish by 85% and 8.21%, respectively. Coated samples had lower L* values. However, samples with sweet potato starch-based batter had better textural properties. The results of this study suggest that edible coating in combination with a batter containing sweet potato starch could be useful in reducing the fat-uptake reduction and improve the physicochemical properties of the fried fish.